A phase III, single-arm, 6-month trial of a wide-dose range oral testosterone undecanoate product - Bernstein, James S.; Dhingra, Om P. (Therapeutic advances in urology, 2024)
Background: Oral testosterone undecanoate (TU) formulations may provide effective, safe, and easily titratable testosterone replacement therapy. Objective: Demonstrate efficacy and safety of a novel oral TU formulation. Design: An open-label, single-arm, multi-center trial treated 155 hypogonadal men for 180 days. Treatment began at 200 mg TU twice daily with meals; doses were titrated over two 28-day cycles to between 100 and 800 mg TU daily, measuring average testosterone (T Cavg) after 90 days. Ambulatory blood pressure monitoring (ABPM) occurred at baseline, 120, and 180 days. Methods: Titrations used a randomized blood sample taken 3-, 4-, or 5-h post-morning dose. Outcomes used sodium fluoride/ethylenediaminetetraacetate plasma testosterone (T) values; serum results were also reported. Blood pressure (ABPM and in-clinic) was evaluated for change from baseline. Results: After titration, 87.8% of KYZATREX™ treated participants (worse-case scenario) and 96.1% of 90-day completers achieved eugonadal mean plasma T values. Serum T Cavg was 452 ng/dL and maximum T concentrations (T Cmax) met all FDA criteria. Participant eugonadal percentages were comparable across subgroups for age, weight, and body mass index. Diet had no effect on participant eugonadal percentages. KYZATREX was well tolerated, with no drug-related serious adverse events (SAE) and one adverse drug reaction (hypertension) observed in 2% or more of participants. Systolic ambulatory blood pressure increased 1.7 mmHg (95% confidence interval: 0.3–3.1). At baseline, 36% of 155 participants were receiving anti-hypertensive medication and 22% were diabetic. No dose increases occurred in existing anti-hypertensive medication; five participants (3.2%) started anti-hypertensive medication. Conclusion: KYZATREX provided safe and effective testosterone levels within the normal range in hypogonadal male study participants. Clinical trial registration: URL: https://clinicaltrials.gov/ unique identifier NCT04467697, conducted under NCT03198728. Post-completion, clinicaltrials.gov requested creation of the separate NCT04467697 identifier. All subjects were recruited under NCT03198728.